Platelet Adhesion to Collagen in Subtypes of Type I von Willebrand’s Disease Is Dependent on Platelet von Willebrand Factor - d'Alessio, Patrizia; Zwaginga, Jaap Jan; de Boer, Hetty C; Federici, Augusto B; Rodeghierio, Francesco; Castaman, Giancarlo; Mariani, Guglielmo; Msnnucci, P Mannuccio; de Groot, Phillip G; Sixma, Jan J (Thrombosis and Haemostasis, 1990)
Von Willebrand’s disease type I, characterized by low levels of factor VIII coagulant activity (VTII :C), von Willebrand factor antigen (vWF:Ag) and ristocetin cofactor activity (RiCof) (1), can be subdivided on the basis of platelet von Willebrand factor into subtype platelet normal, platelet discordant, and platelet low (2). We have investigated the contribution of platelet von Willebrand factor in these various subtypes to platelet adhesion using the rectangular perfusion chamber of Sakariassen et al. (3) with fibrillar collagen or a fibroblast matrix as adhesive surfaces. Platelet adhesion to fibrillar collagen was decreased in all subtypes of von Willebrand’s disease, but not as low as in severe von Willebrand’s disease. A close correlation was observed between platelet adhesion to collagen and plasma vWF:Ag in severe von Willebrand’s disease, subtype platelet low, subtype platelet discordant, and normal controls. The platelet adhesion in subtype platelet normal was higher than expected from the plasma vWF: Ag level. Perfusions in which washed platelets were added to a human albumin solution together with red blood cells gave similar adhesion values in subtype platelet normal and normal controls; adhesion was decreased in subtype platelet discordant, and the lowest values were found in subtype platelet low and in severe von Willebrand’s disease. These data indicate that platelet von Willebrand factor may contribute to platelet adhesion, when plasma von Willebrand factor is low. Perfusion studies over a fibroblast matrix gave similar low adhesion values for subtype platelet low and platelet normal, indicating that the contribution of platelet von Willebrand factor can only be observed on a strongly activating surface such as fibrillar collagen.